2016
DOI: 10.1371/journal.pone.0163818
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Legionella pneumophila Isolates in the Province of Quebec from 2005 to 2015

Abstract: Legionella is found in natural and man-made aquatic environments, such as cooling towers and hot water plumbing infrastructures. Legionella pneumophila serogroup 1 (Lp1) is the most common etiological agent causing waterborne disease in the United States and Canada. This study reports the molecular characterization of Lp strains during a 10 year period. We conducted sequence-based typing (SBT) analysis on a large set of Lp isolates (n = 284) to investigate the province of Quebec sequence types (STs) distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…ST1 has been described by numerous studies, amongst a few other STs, as a main causative agent of LD globally, supporting its high pathogenicity [37,38]. Moreover, in contrast to other highly pathogenic clinical strains rarely isolated from the environment, ST1 has been shown to be among the predominant environmental Lp sg1 strains [22,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…ST1 has been described by numerous studies, amongst a few other STs, as a main causative agent of LD globally, supporting its high pathogenicity [37,38]. Moreover, in contrast to other highly pathogenic clinical strains rarely isolated from the environment, ST1 has been shown to be among the predominant environmental Lp sg1 strains [22,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The same report found that 49% of environmental Lp1 isolated from US facilities with no known disease association were ST1. The clinical and environmental presence of ST1 is not unique to the US but has been reported widely, including in Canada [ 4 6 ], England and Wales [ 7 ], mainland Europe [ 8 16 ], the Middle East [ 17 , 18 ], Australia [ 19 ], and several countries in Asia [ 20 24 ]. It has been proposed that ST1 “Paris” group strains (i.e., isolates with Lp strain Paris-like PFGE and microarray patterns) may represent a homogeneous Lp subpopulation [ 25 ], thus requiring high-resolution genetic analyses to uncover rare polymorphisms among isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-SELEX was used to select aptamers binding specifically to lp120292. This strain was selected because it was involved in the Quebec City Outbreak in 2012 47 . To mimic the physiological state of Lp in water system, Lp cells were grown to post-exponential phase and suspended in Fraquil for 24 h at 25 °C to induce starvation and the associated morphological and physiological changes 43,44 .…”
Section: Resultsmentioning
confidence: 99%